Relationship between accommodation of the stent and triple stent in aortic anomaly and length change (International Seven Journal of Multidisciplinary, 2023)
Among aneurysm treatments, endovascular treatment of the abdominal aorta with stents is the most widely applied alternative today. The aim of this study is to determine a mathematical algorithm that allows defining an equation to predict the final length after stent catheter release in the implantation of one stent or three stents (triple stent). To establish the mathematical equation, a self-expandable Lumini® nitinol stent, manufactured by Braile® Biomédica (Brazil), inserted in a tube of known diameter, was used. To obtain the equation, measurements of the dimensional variation of the cells were performed from the insertion diameter to the zone of free expansion of the stent, where the cells would be in their geometric shape of recovery by the memory of the material, and where there is no more dimensional variation and with the processing of the results, a mathematical model was obtained that allows predetermining the change of extension for each stent applied in the treatment, depending on the diameter in which it will be inserted. DOI: 10.56238/isevmjv1n2-002